НЕМИС АДАБИЁТИДА АБУЛҚОСИМ ФИРДАВСИЙ ҚИСМАТИНИНГ БАДИИЙ ТАЛҚИНЛАРИГА ДОИР (Scientific journal of the Fergana State University, 2023)
The article is devoted to Eastern poetry, especially to German romantic literature of Persian classic literature, to open effective influence to Goytе and Hayne creative works  as well as it shows  different treats about destiny of  Abulkasim Firdausi in great German creative works